2011
DOI: 10.3109/14767058.2011.572310
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy in women with systemic lupus erythematosus: a retrospective study of 111 pregnancies in Chinese women

Abstract: In general, lupus in pregnancy in the Chinese population is generally similar to other cohorts. Pregnancies can be successful in most women with SLE. However, an increase in SLE activity can occur in a significant number of patients, even those who are well controlled. Adverse fetal outcome including fetal loss, preterm birth, and SGA increases significantly with SLE flares during pregnancy with preeclampsia/eclampsia, thrombocytopenia, and active SLE serving independent predictors of adverse fetal and materna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
51
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 27 publications
5
51
2
2
Order By: Relevance
“…Overall, the numbers of malformations among infants of patients were small, and the present study did not have power to examine the differences in specific birth defects. Two studies published before 2000 reported on congenital malformations, with a frequency of 2-3% in children of patients with SLE or other connective tissue diseases (10,11), but a Chinese study reported congenital malformations in 6% of patients in the period 1990 -2008 (9). The higher occurrence of congenital malformations in more recent studies may be explained by improved routines for reporting malformations.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Overall, the numbers of malformations among infants of patients were small, and the present study did not have power to examine the differences in specific birth defects. Two studies published before 2000 reported on congenital malformations, with a frequency of 2-3% in children of patients with SLE or other connective tissue diseases (10,11), but a Chinese study reported congenital malformations in 6% of patients in the period 1990 -2008 (9). The higher occurrence of congenital malformations in more recent studies may be explained by improved routines for reporting malformations.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies have also found fewer live births in women with SLE than in the general population (6,7,9,11), but few studies have examined first and subsequent births separately. One previous study of 313 women with SLE who had first births reported a rate of perinatal death of 4.8% (40).…”
Section: Discussionmentioning
confidence: 99%
“…The seizure risk in SLE is increased in patients with higher disease activity at baseline, prior neuropsychiatric SLE disease, or who are positive for anticardiolipin and anti‐Smith antibodies 3. However, an increase in SLE activity can occur in a significant number of patients, even with well‐controlled disease 4. The present patient had already been weaned off medications and her SLE activity had been stable throughout pregnancy.…”
Section: Discussionmentioning
confidence: 66%
“…Das Risiko für einen Abort bei einem aktiven Lupus vor oder in der Schwangerschaft wird sogar mit 17% vs. 2% angegeben, das für eine Frühgeburt mit 53,2% vs. 8,8% und für einen Small-for-gestationalage-Fetus mit 40% vs. 5,5%, jeweils verglichen mit Patientinnen, die sich zum Zeitpunkt der Schwangerschaft in Remission befanden [20]. Den schlechtesten Schwangerschaftsausgang mit den meisten frühen Frühgeburten und den niedrigsten Geburtsgewichten hatten Patientinnen mit einer Lupuserkrankung und einem Antiphospholipidsyndrom [13].…”
Section: Komplikationen In Der Schwangerschaftunclassified